Efforts to Revitalize Pancasila Values in Building National Character and Global Citizenship - Rizki Fitria Ritonga; Panggih Nur Adi; Fitria Anjar Sari; Siti Zahara Saragih (JED (Jurnal Etika Demokrasi), 2024)
Revitalize Pancasila in shaping national character and global citizenship in this era of globalization are not easy to do because if this is not implemented immediately, more and more new problems will arise which will even be very detrimental to the younger generation in the future. This research is a library research (Library Research) with a descriptive research design. The results of this research are the result of thinking and studying the meaning of Pancasila in Indonesian society. Revitalization is not just about re-instilling Pancasila, but also having to understand several very important elements to become the focus of revitalizing Pancasila values. The elements that must be understood are how to implement the Pancasila revitalization strategy for millennial youth (the Pancasila strategy through religious teaching values, and the Pancasila revitalization strategy in the reality dimension, ideality dimension and flexibility dimension) and Character formation in the global era in higher education as well as problems and obstacles in implementing Pancasila.